The AIB Membership: Who We Are, And What We Are Interested In - Ervin, Marlene; Toyne, Brian (Journal of International Business Studies, 1987)
The AACSB accreditation guidelines of 1974, and the subsequent growth in international business education, add considerably to the need for a clearer understanding of the academic qualifications and research activities of those who are called upon to teach international business subjects. This paper presents information on the educational backgrounds, institutional affiliations, and research interests of the Academy of International Business (AIB) membership. Where appropriate, a distinction is made between members affiliated with U.S. institutions and members affiliated with non-U.S. institutions.